A community-led initiative to de-risk and advance Parkinson’s disease therapeutic targets - Alexandra Vaiana; Jonathan Behr; Ryan Birol; Cornelis Blauwendraat; Bradford Casey; Kushan Chowdhury; Martin Citron; Joshua Crapser; Victoria Dardov; Fiona Ducotterd; Sonya Dumanis; John Dunlop; et al. (npj Parkinson's Disease)
Abstract Identifying effective therapeutic targets for Parkinson’s disease (PD) is challenging, with no current disease-modifying therapies available. To address this, The Michael J. Fox Foundation for Parkinson’s Research launched the Targets to Therapies (T2T) initiative, uniting experts to prioritize and validate promising targets. T2T aims to develop validation strategies, create comprehensive target data profiles, and build tools to support drug development, ultimately accelerating the discovery of new therapies for PD patients.